2009
DOI: 10.1152/ajprenal.00130.2009
|View full text |Cite
|
Sign up to set email alerts
|

A new role for vitamin D receptor activation in chronic kidney disease

Abstract: Valdivielso JM, Cannata-Andía J, Coll B, Fernández E. A new role for vitamin D receptor activation in chronic kidney disease. Am J Physiol Renal Physiol 297: F1502-F1509, 2009. First published July 22, 2009 doi:10.1152/ajprenal.00130.2009.-Vitamin D has proven to be much more than a simple "calcium hormone." The fact that the vitamin D receptor has been found in cells not related to mineral metabolism supports that statement. The interest of nephrologists in vitamin D and its effects beyond mineral metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 130 publications
(90 reference statements)
1
24
0
1
Order By: Relevance
“…Vitamin D has been considered the firstline therapy to suppress PTH levels for ESRD patients with SHP (Bhan and Thadhani 2009;Patel and Singh 2009). Vitamin D has a wide range of beneficial effects besides PTH suppression, including modulating immune response and cell differentiation (Nagpal et al 2005;Valdivielso et al 2009). Because of these effects of vitamin D, it may offer new means to control the inflammatory state of ESRD patients, and vitamin D administration has been shown to improve mortality in HD patients (Teng et al 2003;Teng et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D has been considered the firstline therapy to suppress PTH levels for ESRD patients with SHP (Bhan and Thadhani 2009;Patel and Singh 2009). Vitamin D has a wide range of beneficial effects besides PTH suppression, including modulating immune response and cell differentiation (Nagpal et al 2005;Valdivielso et al 2009). Because of these effects of vitamin D, it may offer new means to control the inflammatory state of ESRD patients, and vitamin D administration has been shown to improve mortality in HD patients (Teng et al 2003;Teng et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important reasons was that the reduction/absence of kidney α1-hydroxylase, which mediates the final hydroxylation step of 25(OH)D to 1,25-(OH) 2 D, could lead to the vitamin D deficiency in CKD patients. Vitamin D deficiency causes parathyroid hyperplasia and increased parathyroid hormone; the consequent hyperparathyroidism and hyper-phosphatemia are important risk factors for mortality in CKD patients [23,24]. Accordingly, vitamin D treatment is associated with a reduced rate of cardiovascular diseases (CVDs) and mortality [25].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…Combination therapy with a RAS inhibitor and a vitamin D analog was found to markedly improve renal injuries in the diabetic vitamin D receptor null-mutant mice which developed more severe renal injuries because of more robust RAS activation [30]. Another study found that combined therapy with losartan and paricalcitol completely reduced proteinuria in a model of experimental diabetic nephropathy, suggesting that the combination of an ACE inhibitor or an ANG II receptor blocker plus a VDRA may be a good therapeutic option [23,24].…”
Section: Diabetic Nephropathymentioning
confidence: 99%
See 2 more Smart Citations